Strategi Fundraising YAPPIKA-ActionAid Melalui Media Online - Adniy, Syeira Rifdah; Irfan, Maulana (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2024)
In an era of rapid technological development, the use of online media has become a highly relevant strategy in fundraising for non-profit organizations. As one of the non-profit organizations that survived to this day, YAPPIKA-ActionAid has a fundraising strategy in fulfilling the implementation of the program. This article aims to describe the fundraising strategy at YAPPIKA-Actionaid through online media, with an emphasis on a multichannel fundraising approach. Using a literature review method, this research describes the various fundraising strategies used by YAPPIKA-ActionAid, including telefundraising, online fundraising, crowdfunding, and community fundraising. An in-depth analysis of each strategy is presented and focuses on how YAPPIKA-ActionAid utilizes technology and online media to achieve their fundraising goals. The conclusion of this article emphasizes the importance of fundraising strategies for social service institutions and the success of YAPPIKA-ActionAid in utilizing online media with a successful multichannel fundraising strategy to achieve sustainability in funding and provide a positive impact on the communities they serve.